A scattered life: the lived experiences of Rohingya refugee mothers in Malaysia - Arshad, Munira; Islam, Arshad (International Institute of Islamic Civilisation and Malay World (ISTAC), IIUM, 2018)
This phenomenological study explores the lived experience of refugee mothers in Malaysia, specifically Rohingya asylum seekers (the most persecuted Muslim minority from Myanmar), using a qualitative research design. Semi-structured, face-to-face, in-depth interviews were held with 20 Rohingya refugee mothers with the aim of providing rich description of the lived experiences related to mothering among refugee and asylum seeking women in Malaysia, thereby filling a significant gap in the research literature. The mothers shared a range of lived experiences that affected their experiences as mothers, including negotiating an opaque and hostile asylum system, and unemployment leading to poor living conditions. Children’s education, well-being, and religion were found to be coping mechanisms that enabled them to feel comforted. As the experiences of these mothers were threatening, they were inhibited from giving the best to their children, yet some of the mothers developed a sense of resilience in dealing with their situation. The implications of the findings are discussed in light of the roles that government agencies and professional bodies share when working with refugee mothers.